Superficial soft tissue biphasic synovial sarcoma with apocrine differentiation in the glandular component: a report of two cases - Shelekhova, Ksenya V; Calonje, Eduardo; Grossmann, Petr; Kacerovska, Denisa; Koudela, Karel; Mirka, Hynek; Michal, Michal; Kazakov, Dmitry V (The American Journal of dermatopathology, 2014)
: The authors present 2 cases of a subcutaneous biphasic synovial sarcoma with marked apocrine differentiation that potentially may be confused with cutaneous epithelial neoplasms, including malignant apocrine mixed tumor or metaplastic carcinoma with an apocrine glandular component. Microscopically, both neoplasms had a biphasic architecture with the epithelial and spindle cell components. The epithelial component was prominent and consisted of simple glands with round lumina and complex glandular structures with intraluminal bridges forming cribriform areas. The glands were lined by cuboidal to columnar cells with eosinophilic or clear cytoplasm manifesting apical apocrine-like and intraluminal eosinophilic secretions. The spindle cell component was less prominent and was composed of relatively uniform or slightly atypical spindle sells surrounding and merging focally with the glandular structures. Immunohistochemically, the tumor cells in both components were positive for vimentin, AE1/AE3, CK7, and epithelial membrane antigen. Desmin, smooth muscle actin, muscle-specific actin, CD34, and S-100 protein were all negative. SYT-SSX1 gene fusion using fluorescence in situ hybridization and RT-PCR methods was detected in both cases.
Keywords: fúzní onkogenní proteiny; Cell Differentiation; apokrinní žlázy; hybridizace in situ fluorescenční; Oncogene Proteins, Fusion; Middle Aged; mužské pohlaví; nádory měkkých tkání; Apocrine Glands; In Situ Hybridization, Fluorescence; Biomarkers, Tumor; polymerázová řetězová reakce s reverzní transkripcí; synoviom; ženské pohlaví; nádorové biomarkery; Humans; lidé středního věku; Sarcoma, Synovial; Soft Tissue Neoplasms; Reverse Transcriptase Polymerase Chain Reaction; buněčná diferenciace; Female; lidé; Male